My grandmother's Chinese kitchen : 100 family recipes and life lessons / Eileen Yin-Fei Lo - Eileen, Yin-Fei Lo
Collects one hundred recipes learned by the author from her grandmother, outlining specific cooking techniques, from stir-frying and steaming to braising and stewing, and including anecdotes about the author and her grandmother.